A structural impact analysis of the fashion system with regards to textile recycling. (2019) - Weber, Sabine
The current fashion system is a linear economy predicated on buy, use and disposal. This leads to high amounts of textile waste on the one side and fibre shortage on the other side. Overcoming this global fibre gap requires a circular fashion system. We conduct a structural analysis to study the direct and indirect influences between the factors, by using a systematic approach based on impact matrix cross-reference multiplication applied to a classification (MICMAC) analysis. The results reduce systemic complexity by defining the most influential factors of the system. The study concludes that government policies should create market incentives to foster a circular economy in the textile system.